EFFECTS OF COMPETENCY-BASED CURRICULUM PLANNING AND ASSESSMENT STRATEGIES ON THE QUALITY OF LEARNING OUTCOMES IN ENGLISH TEACHING IN MACHAKOS SUB-COUNTY, KENYA - EMMAH WANJIRU MURIITHI (Machakos University Press, 2025)
This study focused on the relationship between the implementation of competency based curriculum planning and assessment strategies and the learning outcomes in English teaching in the Machakos Sub-County, Kenya. The objectives of the study were: to establish how the implementation of the new CBC scheming and lesson planning strategies by Teachers of English affects learning outcomes; to establish how Teachers of English’ use of the new CBC assessment strategies affects learning outcomes; to establish how the Teachers of English` attitude towards the implementation of the new CBC affects learning outcomes; to explore the challenges faced by Teachers of English during lesson planning and assessment, in primary schools in Machakos Sub-County, Kenya. The study was guided by the Theory of Visible Learning by John Hattie. The study employed a descriptive survey research design. The research instruments used in the study included: questionnaires for head teachers, teachers, and Curriculum Support Officers. The target population included 91 primary school head teachers, 2 Curriculum Support Officers, 364 Teachers of English, and grade one to six pupils. The study used simple random sampling to select eleven (11) primary schools in the Machakos Sub-County. A total of eleven (11) head teachers were purposively sampled from the eleven schools, and forty-five (45) grade one to grade six teachers of English were purposively sampled, (1993) grade one to grade six pupils were purposively sampled from the eleven schools. One curriculum support officer was randomly sampled from among the three educational zones in the sub county.